THE INFLUENCE OF MOTIVATION AND JOB SATISFACTION ON EMPLOYEE PERFORMANCE AT THE PALOPO CITY EDUCATION OFFICE - Kulsum, Ummi; Citra, Citra; Safira, Alma; Renaldi, Renaldi; Nugraha, Yuda Satria (Jurnal Manajemen, 2024)
In organizational success, one of the factors that influences employee performance is human resources. Human resources are the actors in the entire management process in an organization starting from the level of planning, organizing, directing to evaluating all organizational management activities. Human resources include motivation and job satisfaction. In this research, the data collection techniques used were observation, administering questionnaires and interviews. This research raises the issue of the influence of motivation and job satisfaction on employee performance at the Palopo City Education Office. The population in this study was employees at the Palopo City Education Office, totaling 115 people. Using random sampling technique, 54 people were taken as samples. The research results show that the variables of motivation and job satisfaction simultaneously have a significant effect on employee performance at the Palopo City Education Office. Partially, motivation has a significant effect on employee performance at the Palopo City Education Office, while job satisfaction does not have a significant effect on employee performance at the Palopo City Education Office.